Riba prohibition and social welfare: a socio-legal analysis of islamic economic norms on family and state outcomes - Endang Madali (Global Econedu, 2026)
This study examines the legal implications of usury (riba) on families and the state from the perspective of the sociology of Islamic law. Islamic law regulates all aspects of human life, including economic activities, and prohibits riba because it contradicts the principles of justice and social welfare. The research aims to analyze the relationship between Islamic legal norms concerning riba and their socio-economic impacts on contemporary society. A qualitative approach was employed through the analysis of primary Islamic sources, including the Qur'an and Hadith, supported by relevant academic literature and empirical studies on the effects of usury practices. The findings indicate that riba contributes to social inequality, weakens moral values, reduces family welfare, and creates economic dependency that may threaten national economic stability and sovereignty. These findings demonstrate that the prohibition of riba is not merely a theological doctrine but also a legal and social mechanism designed to protect public welfare. Therefore, greater collective awareness and the implementation of Sharia-based economic principles are necessary to foster justice, social harmony, and sustainable prosperity for both families and the nation.